Desmoid-type fibromatosis of the splenic hilum: A rare tumor at an unusual location - Ana Sanchez-Gollarte (Nigerian Journal of Surgery, 2020)
Desmoid-type fibromatoses (DTFs), also known as desmoid tumors, are benign but infiltrative neoplasms that often appear next to previous surgical site. Intra-abdominal tumors usually involve the mesentery, but splenic hilum is an unusual localization. We present a case of a desmoid tumor of the splenic hilum laparoscopically resected in a 70-year-old male with a previous history of chromophobe renal cell carcinoma and ocular spindle melanoma. Although benign, desmoid tumors might be infiltrative and produce serious complications. Treatment remains controversial, ranging from surgery and medical therapies to observation. Management of DTF must be individualized, considering the risk of complications and recurrence.